Prehistory and Ideology in Cold War Southeast Asia: The Politics of Wartime Archaeology in Thailand and the Democratic Republic of Vietnam, 1954–1975 - Peleggi, Maurizio (MDPI AG, 2023)
10.3390/histories3020008